If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H(x) = 0.75 + 18(x) Multiply H * x xH = 0.75 + 18(x) Solving xH = 0.75 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -18x + xH = 0.75 + 18x + -18x Combine like terms: 18x + -18x = 0 -18x + xH = 0.75 + 0 -18x + xH = 0.75 Reorder the terms: -0.75 + -18x + xH = 0.75 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 -0.75 + -18x + xH = 0.00 The solution to this equation could not be determined.
| 2x-7y+6=3(y-x)-4 | | 2(x-4)=-5 | | 3(2-4)=6(-2) | | 5d+6n=t | | (0)-3y=6 | | -1x-4=4 | | d-(-3)=100 | | -43=7-8t | | 16(y^2-9)-9x^2=0 | | 3y+7=2y-5 | | 2r^2+4r=2r^2-r | | 5r-13s=76 | | 3(x+4)-2=4 | | 3x-69=3 | | 0-3(-1)=6 | | -7f+4f=6 | | -3(5x+3)+4(6x+1)=43 | | 7+6q=67 | | C^2+4d^2-d^2= | | 6x+3-2x=15 | | -3n+6+5n=7n-8n+9 | | 7y+11=8-5y | | 9x-25=38 | | 2.5+1.5N=F | | n/9-4=-3 | | -3+6+5n=7n-8n+9 | | (n+5)=-2 | | -3(x-5)=4 | | 40-4x=5(4x+3)-5(-8-3x) | | 9x+-3x=36 | | 7+6x=67 | | 6(2x-1)+3=6(2-x)-1 |